Assessing resistance against Alternaria leaf spot in marigold genotypes(Tagetes spp.): A comprehensive in vitro and in vivo study - Sharma, S; Das, A; Bharti; Singh, K P; Panwar, S; Talukdar, A; Arzoo, E; Singh, A; Bisht, P; Bhatia, R (Journal of Horticultural Sciences, 2025)
Marigold (Tagetes spp.) a member of the Asteraceae family, is a globally acclaimed flower crop owing to its significant industrial value. The present study devised an effective screening method utilising a dual approach study, both in vitro and in vivo, for identifying potentially resistant genotypes of marigold. Pathogen isolation from infected plants revealed that 7 out of 10 isolates belong to Alternaria, confirming its prevalent association with leaf spots in marigold. Pathogenicity assessment revealed isolate I-3 as the most virulent isolate, and hence, it was subsequently used for the dual screening programme. Molecular characterization of the virulent isolate based on Internal Transcribed Spacer (ITS) region sequencing revealed its 100% homology with previously reported sequences of Alternaria alternata. Potato dextrose agar and Host-extract media (with dextrose) supported rapid mycelial growth and abundant sporulation. Among 60 genotypes of marigold screened under in vitro and in vivo conditions, AMS-48, AMS-123, Pusa Parv, Pusa Utsav and MGO 3 exhibited moderate resistance. At the same time, Pusa Basanti Gainda, Pusa Deep and Tagetes minuta selections were found to be highly susceptible. These findings were consistent under both conditions, validating the screening methods. The moderately resistant genotypes can be pivotal in marigold breeding programs for developing resilient marigold varieties.